2017
DOI: 10.4265/bio.22.121
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the High-Expression of Proline Transporter PutP to the Adaptation of <i>Escherichia coli</i> to High Salinity

Abstract: The effect of the amount of the proline transporter PutP expression on the mechanism of adaptation of E. coli cells to high salinity was analyzed. The PutP gene derived from the E. coli expression plasmid was introduced into the E. coli cell, and a high PutP expression strain was developed. At 1.2 M NaCl culture condition, the growth of normal E. coli cells was inhibited, whereas high ProP expression cells showed growth under 2.5 M NaCl conditions. The uptake of proline by E. coli as a compatible solute and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, the growth of E. coli in hyperosmotic nutrient-poor solutions in this study may not be probable. Growth of E. coli was suppressed in nutrient-rich medium containing NaCl in a range of approximately 1 -5.8 % (Sasaki et al, 2009) , which covers hyperosmotic condition (3.5 % and 5.0 % NaCl) in this study. In addition, bacterial growth would be suppressed more in nutrient-poor system than in nutrient-rich system.…”
Section: Ns_25 Ns_37 S_37mentioning
confidence: 86%
See 1 more Smart Citation
“…However, the growth of E. coli in hyperosmotic nutrient-poor solutions in this study may not be probable. Growth of E. coli was suppressed in nutrient-rich medium containing NaCl in a range of approximately 1 -5.8 % (Sasaki et al, 2009) , which covers hyperosmotic condition (3.5 % and 5.0 % NaCl) in this study. In addition, bacterial growth would be suppressed more in nutrient-poor system than in nutrient-rich system.…”
Section: Ns_25 Ns_37 S_37mentioning
confidence: 86%
“…Simultaneously, osmoprotectants such as K + , glutamate, proline, and glycine betaine were accumulated inside the cells from the culture medium. Meanwhile, the cells in hyperosmotic environment synthesized trehalose while they released toxic components such as putrescine (Dinnbier et al, 1988;Nagata et al, 2005;Sasaki et al, 2009;Weber et al, 2006) . Thus, those osmotic responses may help E. coli cells survive NaCl stress.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the salt tolerance of Bifidobacterium longum and E. coli can be increased through the increased expression of a small heat shock protein [ 122 ] and the PutP proline transporter gene [ 123 ], respectively. Furthermore, the ectoine genes, ectABC , of the halophilic bacterium Chromohalobacter salexigens has been successfully engineered into an E. coli strain to increase halotolerance [ 124 ], while the heterologous expression of a betaine uptake system, BetL has helped to increase the tolerance of Lactobacillus salivarius UCC118 to multiple stresses, including osmotic stress [ 125 ].…”
Section: Genetic and Microbial Engineering Of Biomining Microorganmentioning
confidence: 99%